Stable Zinc-Based Metal-Organic Framework Photocatalyst for Effective Visible-Light-Driven Hydrogen Production - Li-Long Dang; Ting-Ting Zhang; Ting-Ting Li; Tian Chen; Ying Zhao; Chen-Chen Zhao; Lu-Fang Ma (Molecules, 2022)
Herein, a new Zn-MOF material, [Zn(L1)(L2)], 1, was built successfully through a one-pot solvothermal method. The 3D MOF structure was determined by Single X-ray diffraction analysis, IR, and elemental analysis. A series of PXRD tests of 1 after being immersed in different solvents and pH solutions demonstrated the good stability of 1. Interestingly, this material displayed high catalytic activity for the visible-light-driven hydrogen generation under the illumination of white LED in pure water or a mixture of DMF and H2O without additional photosensitizers and cocatalysts. Besides, the studies also showed that the catalytic activity changed constantly as well as the solvent ratio adjustment of DMF and H2O from 4:6 to 2:8. Additionally, the catalytic activity reached the best value (743 μmol g−1 h−1) when the solvent ratio was 4:6. The heterogeneous nature and recyclability of the MOF catalyst, as well as several factors that affect the catalytic activity, were investigated and described in detail. Moreover, the photocatalytic mechanism for the hydrogen generation of 1 was also proposed based on the fluorescence spectra and UV-vis absorption.